A quantitative evaluation model to measure the disassembly difficulty; application of the semi-destructive methods in aviation End-of-Life. Issue 12 (17th June 2016) - Zahedi, Hamidreza; Mascle, Christian; Baptiste, Pierre
Abstract : Sustainable decommissioning of aircraft with a high content of metallic and non-metallic components is a current challenge in the industry. This process has historically appeared to be economically, environmentally and socially unviable. Literature indicates that, unlike entirely destructive and totally non-destructive techniques, semi-destructive disassembly may bring significant benefits. However, despite their use in a wide variety of applications, there are currently no feasible solutions on how to measure the associated physical difficulties and required efforts without any dependencies on expert views or filling out spreadsheet-like forms. In this paper, a new model is developed to accurately evaluate the disassembly easiness of an airframe quantitatively incorporating both product and process features. Based on a real disassembly of a passenger jet, the cutting and thrust force vectors are selected to evaluate and find the best operation sets. An airliner Horizontal Stabiliser is analysed as a case study. The results indicate that minor drilling, as a hybrid operation, can reduce the disassembly efforts significantly while offering an increased material recovery chance. Such quantitative evaluation can help to: proceed with a viable End-of-Life strategy; and implement newer approaches like automated disassembly by designing better disassembly robots, tool selection and process control.